The output effects of commodity price volatility: Evidence from exporting countries - Michael Hachula; Sebastian Hoffmann (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2015)
Empirical evidence indicates that high oil price volatility has a dampening effect on output in countries that import commodities. Many countries, however, gain important revenues from commodity exports. This paper investigates the output effects of commodity price volatility in commodity exporting countries accounting for both oil and non-oil commodities. To that aim, we construct country specific commodity price indices for a sample of oil and non-oil commodity exporters. We find a significant negative impact of price volatility on real output for oil exporters. Our results for exporters of other commodities, however, suggest that the volatility effect is a peculiar feature of oil and not generalizable to a broad basket of commodities.
Keywords: C32; O13; Q43; 330; commodity price uncertainty; commodity exporters; VAR-MGARCH-in-mean